2011
DOI: 10.4103/1995-705x.90903
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression symptoms in chest pain patients referred for the exercise stress test

Abstract: Introduction:As chest pain is an important symptom of coronary artery disease (CAD), the presentation of the symptom often prompts referral to a cardiologist for further investigation. The aim of the present study is to determine the prevalence of anxiety and depressive symptoms in patients referred to a cardiology outpatient clinic for performing the stress test.Patients and Methods:Two hundred and fifty consecutive outpatients referred for evaluation of chest pain by the stress test at a government cardiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 8 publications
0
20
0
1
Order By: Relevance
“…Patients with negative tests had significantly higher scores for anxiety and higher depression scores than those with positive tests. [8] There is positive and (Statistical) significance (p<0.05) correlation between symptom duration and DSSS score, it means that if (Symptom) duration of chest pain (Increases) than dsss total score will increase. This finding is supported by other study in which the prevalence of depressive disorders in patients with AMI 1 month after the cardiac event was stated as 59.5% by Strik et al, which was higher than the other studies.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with negative tests had significantly higher scores for anxiety and higher depression scores than those with positive tests. [8] There is positive and (Statistical) significance (p<0.05) correlation between symptom duration and DSSS score, it means that if (Symptom) duration of chest pain (Increases) than dsss total score will increase. This finding is supported by other study in which the prevalence of depressive disorders in patients with AMI 1 month after the cardiac event was stated as 59.5% by Strik et al, which was higher than the other studies.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with chest pain and no evidence of significant CAD can continue to have physical limitations and a poor quality of life [29,30] . The pathophysiology of such pain is unknown, although prior studies have suggested possible mechanisms such as endothelial and microvascular coronary dysfunction [31][32][33] as well as psychological factors [34] . Traditionally patients with symptomatic non obstructive disease are a difficult cohort to manage as symptoms are often indistinguishable from those with significant CAD [35] .…”
Section: Discussionmentioning
confidence: 99%
“…It may be a symptom of coronary artery disease or myocardial infarction, which is one of the most terrifying conditions for patients [7][8]. According to numerous studies, in emergency departments the diagnosis of organic cause of the ailment is excluded in 30% to 77% of patients [9][10][11][12]. A comparable proportion of patients in primary health care, i.e.…”
Section: Psychosomatic Syndromes In Hospital Emergency Department Prmentioning
confidence: 99%